Barriers for Cataract Surgical Services in West Java Province of Indonesia - Nina Ratnaningsih; Mayang Rini; Aldiana Halim (Majalah Oftalmologi Indonesia, 2016)
Background: Prevalence of blindness in West Java province according to RAAB survey is 2.8% withconfidence interval 2.0-3.5%, and cataract is the main cause with the proportion of 77.1%. It meansthere are 257,600 blind people of 50 and above, 198,609 of them have cataract blindness. In the termof cataract problems, West Java government has been implementing the prevention of blindness andlow vision program since 2005, but backlog of cataract is still high. Lots of barriers on cataract surgicalservices program come from provider and population. Five main kind of barriers come from populationare costs, distance, social and culture, community awareness, and trust to provider. Information ofbarriers is important for program planning to overcome the barriers. The purpose of this research is toreport the barriers of cataract surgical services program in West Java province according to RAABsurvey.Methods: This study is West Java population-based cross sectional study using Rapid Assessment ofAvoidable Blindness (RAAB) protocol, with multistage cluster sampling that was conducted in 2014.Results: Cataract blindness prevalence was 0.8% (95% CI 0.2-1.3%) for male and 2.2% (95% CI 1.4-2.9%) for female. Cataract surgery was performed more in male (44.1%) than female (25.8%). Mainbarriers in male group of cost, need no felt, fear, and unaware of treatment are possible; while thebarriers in female group were cost and fear. An unaware of the treatment is possible.Conclusion: The barriers of cataract surgical services in West Java were cost, need no felt, fear, andunaware of the treatment are possible. We need to manage the cost and increase community awarenessand willingness of cataract surgery to encounter the problem cataract blindness and visual impairmentin West Java province.